Indicator power spectra: surgical excision of non-linearities and covariance matrices for counts in cells. Issue 1 (22nd October 2021) - Repp, Andrew; Szapudi, István
ABSTRACT: We here introduce indicator functions, which identify regions of a given density in order to characterize the density dependence of clustering. After a general introduction to this tool, we show that indicator-function power spectra are biased versions of the linear spectrum on large scales. We provide a calculation from first principles for this bias, we show that it reproduces simulation results, and we provide a simple functional form for the translinear portion of the indicator-function spectra. We also outline two applications: First, these spectra facilitate surgical excision of non-linearity, and thus, significantly increase the reach of linear theory. Second, indicator-function spectra permit calculation of theoretical covariance matrices for counts-in-cells (CIC), facilitating parameter estimation with complementary CIC methods.